Distributed fixed-time secondary control of an islanded microgrid via distributed event-triggered mechanism. Issue 5 (4th May 2023) - Xu, Deming; Li, Ze; Cui, Guozeng; Hao, Wanjun
Abstract : The fixed-time secondary control problem for an islanded microgrid (MG) through an event-triggered communication mechanism is investigated in this paper. A distributed event-triggered fixed-time control strategy is proposed to achieve frequency and voltage secondary restoration. And a proportional active power-sharing is also achieved through an undirected topology. The given control protocol using frequency, voltage magnitude and active power measurement values of neighboring distributed generations only when the predefined event-triggered condition is satisfied. In comparison with the periodic communication way, the presented method exhibits excellent performance in alleviating communication burden and promoting control efficiency. Moreover, compared with conventional asymptotic control algorithms, the objectives of islanded MG secondary control are obtained within a fixed settling time by using the presented fixed-time control approach. The estimation of settling time is unrelated to any initial states. Several simulation experiments are conducted to demonstrate the effectiveness of the proposed control scheme.